The german raccoon (procyon lotor) population as potential rabies reservoir species - Vos, A.; Finke, S.; Habla, C.; Freuling, C.; Teifke, J.; Köllner, B.; Müller, T. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Until recently, the red fox (Vulpes vulpes) was considered the only reservoir species for terrestrial wildlife rabies in Europe. However, since the late 1980s another host species has emerged in North- and East Europe; the raccoon dog (Nyctereutes procyonoides). Interestingly, several other potential rabies reservoir species occur in Europe but without evidence that these animals play any role in the spread of the disease; golden jackals (Canis aereus) in Southeast Europe, the small Indian mongoose (Herpestes auropunctatus) inhabiting parts of the Adriatic coastal region, and the raccoon (Procyon lotor) in most parts of Europe. Especially in (semi-) urban areas in Germany, extreme high raccoon population densities have been observed (approx. 100 animals/km²). To investigate the possibility that raccoons in Germany could become a reservoir species in case of re-emergence of rabies in Germany the susceptibility of the ´local’ raccoon population was investigated. Wild caught animals were inoculated with the most likely lyssavirus variants to infect the German raccoon population. It was shown that the German raccoons were fully susceptible for a dog and raccoon rabies virus (RABV) variant. Five of 6 raccoons inoculated with a fox RABV isolate showed subsequently clinical signs. In contrast to foxes, none of the infected raccoons succumbed to rabies after infection with European Bat Lyssavirus Type 1 (EBLV-1); although all these raccoons seroconverted. The most likely event that a German raccoon will come in contact with a lyssavirus is through contact with an infected bat. It can therefore be a reassuring thought that based on the results of this study raccoons are highly refractory to EBLV-1 virus infection.